Modal Sosial Pedagang Angkringan dalam Mempertahankan Usaha di Kota Pekanbaru - Putri Nabila Nur Nasution; Rina Susanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Social capital includes social networks, norms, and beliefs of Angkringan vendors in maintaining business in Pekanbaru City. This study aims to find out the elements of social capital between semi-independent Angkringan vendors and suppliers and elements of social capital between Angkringan vendors and consumers in Pekanbaru City using Social Capital Theory by Robert D. Putnam. This study was conducted in Jl. Arifn Ahmad and Jl. H.R.Soebrantas, Pekanbaru City. The research method used was descriptive qualitative. The data collection techniques used observation, in-depth interviews, and documentation. The subjects of the study were 9 people consisting of 3 additional subjects and 6 main subjects who were selected systematically using a purposive sampling technique. The results of the study showed that social capital is an important factor in maintaining Angkringan business. The three main elements of social capital are networks, norms, and beliefs, which have a significant role in supporting business sustainability. Semi-independent Angkringan vendors tend to rely on suppliers, so a relationship based on trust and cooperation through social networks is the key to sustaining their business. The same applies to the relationship with consumers; vendors really require consumers to ensure business continuity. Thus, social capital is the main foundation for maintaining and developing Angkringan business.